Algicidal substances of Brevibacillus laterosporus and their effect on red tide organisms - Liu, Shanshan; Yu, Zhiming; Wu, Zaixing; Cao, Xihua; Cheng, Ruihong; Song, Xiuxian (Frontiers in Marine Science, 2023)
Herein, the algicidal effects of Brevibacillus laterosporus on typical red tide organisms were investigated. Through comparative analysis of the fermentation solution, sterile filtrate and bacterial body, it was found that this strain mainly exerts its algicidal function by secreting algicidal substances. In this paper, we established a method for extracting the algicidal substances of B. laterosporus and systematically investigated their features and effect on Heterosigma akashiwo. The results showed that the algicidal substances are a mixture of compounds all with molecular weights less than 3500 Da, with those below 100 Da producing 45% of the algicidal effect; these are more polar and best extracted with methanol. The algicidal substances are stable over a range of temperatures (-80.0 to 70.0 °C) and pH values (4.0-8.0). The algicidal substances caused most H. akashiwo cells to rupture within 24 h. In the remaining cells, the algicidal substances activated the antioxidant system and reduced their metabolic activity, leading to apoptosis, as observed by cell crumbling and a reduction in membrane potential. The responses of different algal cell surface structures to the algicidal substances were also compared and analyzed. It was concluded that these algicidal substances can act on the cell membrane and change its permeability, allowing entry of the algicidal substances to produce an algicidal effect.